2016
DOI: 10.1177/0018726716631808
|View full text |Cite
|
Sign up to set email alerts
|

From social context and resilience to performance through job satisfaction: A multilevel study over time

Abstract: Among job attitudes, overall job satisfaction has received the greatest attention in organizational research and it has frequently been suggested as the key factor influencing employees' performance. Although it reflects individual experiences, job Many people spend a significant amount of time in their workplace and the feelings of work-related satisfaction or dissatisfaction contribute to overall quality of life and psychological well-being (Judge and Watanabe 1993;Wright et al., 1999).Beyond the value of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 77 publications
0
72
0
4
Order By: Relevance
“…For example, at an individual level, some studies show there to be a direct positive relationship between resilience and job performance or productivity (Luthans, Avolio, Walumbwa, & Li, 2005;Shatté, Perlman, Smith, & Lynch, 2017), whereas others find null or weak relationships between both variables (Youssef & Luthans, 2007). Actually, recent research has shown that there is an indirect connection between resilience and performance via job satisfaction (Meneghel, Borgogni, Miraglia, Salanova, & Martínez, 2016). Note, these studies have considered variables at an individual level.…”
Section: Consequences Of Resilience At Work: the Mediating Role Of Olmentioning
confidence: 99%
“…For example, at an individual level, some studies show there to be a direct positive relationship between resilience and job performance or productivity (Luthans, Avolio, Walumbwa, & Li, 2005;Shatté, Perlman, Smith, & Lynch, 2017), whereas others find null or weak relationships between both variables (Youssef & Luthans, 2007). Actually, recent research has shown that there is an indirect connection between resilience and performance via job satisfaction (Meneghel, Borgogni, Miraglia, Salanova, & Martínez, 2016). Note, these studies have considered variables at an individual level.…”
Section: Consequences Of Resilience At Work: the Mediating Role Of Olmentioning
confidence: 99%
“…Whereas some studies have emphasised the unique traits of individuals who exhibit resilience (Earvolino‐Ramirez, ; Windle, ), others have aimed at understanding the context (Meneghel, Borgogni, Miraglia, Salanova, & Martínez, ) and processes that lead teams and individuals to become resilient and withstand difficulties (Luthar, Cicchetti, & Becker, ; Mahoney & Bergman, ; Morgan, Fletcher, & Sarkar, ). Thus, unlike its original conceptualisation in physics, resilience is a capacity that develops over time, and comes from rather ordinary qualities such as self‐regulation, a positive view of the self, and relationships with others (Masten, ).…”
Section: Interorganisational Relationships and Organisational Resiliencementioning
confidence: 99%
“…We argue that employees' resilience represents such a personal resource, in that it provides them with discretionary energy from which they can draw to undertake disruptive work behaviours that might add to their organization's well‐being, as well as their own professional success (Caniëls & Baaten, ; Meneghel, Salanova, & Martínez, ; Wolfson & Mulqueen, ). Their resilience and associated desire to learn from difficult work situations also might make the generation of radically new ideas more personally fulfilling and satisfying (Cho, Park, & Dahlgaard‐Park, ; Meneghel, Borgogni, Miraglia, Salanova, & Martínez, ), despite any scepticism or even overt criticism with which these ideas might be received by other members (Deichmann & van den Ende, ).…”
Section: Introductionmentioning
confidence: 99%